Síndrome Burnout relacionado con la inteligencia emocional en los empleados del “Hospital Napoleón Dávila Córdova”, cantón Chone. Diciembre 2020-junio 2021 - Bravo Vera, Julexy Fernanda (2023)
Through the study it was possible to identify the causes that bring about this diagnosed pathology, the research focused on a descriptive design and also on the quantitative method; applying surveys and interviews to staff through the instrument used called Maslach Burnout Inventory, applied to hospital employees, getting to know their opinions about the disease and in turn the one that this causes, what problems affect them; both instruments reflected the emotions that said staff maintains, all this intervenes in their emotional, work and mental performance, likewise it was possible to identify the secondary effects caused, as emotional exhaustion, depersonalization and personal fulfillment. With the results obtained, it was concluded that there are no preventions for this symptomatology, therefore, a prevention plan and the pertinent recommendations were prepared, which were addressed to the Human Talent staff, administrative staff and psychological area, so that they can be applied focusing on decrease the problem; managing to control emotional intelligence and increase the personal and productive development of employees.